2015
DOI: 10.17116/neiro201579534-42
|View full text |Cite
|
Sign up to set email alerts
|

Experience in the use of high-frequency selective percutaneous rhizotomy in trigeminal neuralgia associated with multiple sclerosis

Abstract: These data confirm that PHFSR is a safe, repeatable, and effective method of symptomatic neurosurgical treatment of TN associated with MS and may be recommended in the case of failure/intolerance of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Several studies with a follow-up exceeding one year have investigated the role of surgical procedures designed to lesion the Gasserian ganglion. Procedures were performed chemically by glycerol injections [61, 7072], mechanically by balloon compression [7376], or thermically by radiofrequency thermocoagulation [64, 7779]. Although most patients enrolled in these studies reported complete acute pain relief following the lesioning procedures, the recurrence rate during follow-up and the frequency of adverse events varied widely (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies with a follow-up exceeding one year have investigated the role of surgical procedures designed to lesion the Gasserian ganglion. Procedures were performed chemically by glycerol injections [61, 7072], mechanically by balloon compression [7376], or thermically by radiofrequency thermocoagulation [64, 7779]. Although most patients enrolled in these studies reported complete acute pain relief following the lesioning procedures, the recurrence rate during follow-up and the frequency of adverse events varied widely (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies with more than 1 year of follow-up have examined the role of surgical procedures in repairing damage to the gasserian ganglion. The procedures were performed chemically with glycerol injections (72-75), mechanically with balloon compression (76-79), or thermally (70,(80)(81)(82). Although most of the patients reported complete acute pain relief after the lesion procedures, the recurrence rate during follow-up and the incidence of adverse events varied widely.…”
Section: Methodsmentioning
confidence: 99%
“…A recent retrospective review of long-term outcomes in 42 patients showed that the incidence rates of cases with pain relief after SRS were 62%, 29%, 22%, and 13% after 1, 3, 5, and 7 years, respectively (89). Retrospective studies have compared the efficacy of SRS with gasserian ganglion surgery (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90). These studies have shown that patients who underwent gasserian ganglion surgery experience immediate pain relief and no longer need to resort to AI therapies than patients treated with SRS.…”
Section: Methodsmentioning
confidence: 99%